Corpos ressonantes: canto e cura entre os Tikm'n - Sofia Cupertino Furtado (2017)
The Tikm'n Maxakali people (from Minas Gerais state, Brazil) peoples mobilize diverse therapeutic techniques in their daily lives. Among them, there is the intense presence of practices of Yãmyxop songs for healing purposes. These songs are intimately associated with the person Tikm'n notion and in a particular idea about the human body. In this work, I will relate the conceptions of person and consequently of the body, illness, and healing among the Tikm'n, based on the Yãmyxop songs. Finally, in this case study, I pursue to contextualize the Western notion of a person as an individual in a broader discussion, as well as the relativization process of this concept within anthropological studies.